Personal Opinions about the Social Security System and Informal Employment : Evidence from Bulgaria - Perotti, Valeria; Sánchez Puerta, Maria Laura (World Bank, Washington, DC, 2014)
In this paper the authors analyze the relationship between personal opinions about the social security system and levels of informal employment using data from a recent household survey carried out in Bulgaria. They compare different indicators of job informality, focusing on the lack of social security affiliation as the main indicator. The results suggest that low value is attached to social security affiliation and that knowledge of the social security system is very limited. As a consequence, many workers seem to choose informal jobs because they think that the benefits from being affiliated with the social security system are too low compared with the costs. On the other hand, being affiliated does not seem to matter in terms of overall job satisfaction.